Corporate Digital Responsibility in the Retail Industry: Cameo Case Studies of Two German Retailers - Peter Jones (Athens Journal of Business & Economics, 2023)
Digital technologies bring a wide range of new opportunities, for both retailers and consumers, but retailers face, and may have to address, several new sets of responsibility issues as they progressively introduce these technologies. These responsibilities are increasingly being captured in the concept of corporate digital responsibility (CDR) but CDR within the retail industry has received little, or no attention, in the academic literature. This paper looks to make a small contribution to addressing that gap in the literature. The paper includes some definitions of CDR, an outline of the concept and scope of CDR, two cameo case studies which provide a simple illustration of some of the ways in which the Rewe Group and the Otto Group, two of Germany’s leading retailers, choose to publicly address CDR, and offers some reflections on retailers and CDR. The paper suggests that there are, potential tensions between the retailers’ management of the economic and the social dimensions of CDR, and that there are issues about whose best interests are served by CDR and the difficulties involved in making such judgements.